Spot Urine Albumin to Creatinine Ratio and Serum Cystatin C are Effective for Detection of Diabetic Nephropathy in Childhood Diabetic Patients - Chae, Hyun-Wook (The Korean Academy of Medical Sciences, 2012)
Spot urinary albumin to creatinine ratio (ACR) measurement has been suggested as a surrogate to 24-hr urine collection for the assessment of microalbuminuria, and cystatin C (cysC) is known as an advantageous marker for renal function. The aim of this study was to evaluate the clinical values of spot urinary ACR and serum cysC for the assessment of diabetic nephropathy instead of 24-hr urine microalbumin in children and adolescents with diabetes. A total of 113 children and adolescents (age 12-19 yr, M:F = 47:66) with type 1 or 2 diabetes were enrolled. We evaluated the validity of spot urine ACR and serum cysC, and then compared them to 24-hr urine microalbumin and creatinine clearance. Spot urine ACR was correlated with 24-hr urine albumin excretion (R(2) = 0.828, P = 0.001) and creatinine clearance (R(2) = 0.249, P = 0.017). The ROC curve analysis of serum cysC demonstrated higher diagnostic accuracy than that of serum creatinine (AUC 0.732 vs 0.615). Both the measurements of spot urine ACR and serum cysC might better predict the presence of diabetic nephropathy than 24-hr urine microalbumin in childhood diabetic patients.